A Quasi-Longitudinal Examination of the Cube One Framework (American Journal of Management, 2023)
This paper begins by explaining the nature and premises undergirding the Cube One Framework, insofar as the authors assume that most readers have never heard of it. The Framework is multi- dimensional, focusing on the interests of employees, customers, and the enterprise, and it is also based on multiple fields of inquiry. i.e., Organizational Behavior, Marketing, Operations Management, etc. The present research is the first study to obtain repeated measure data pertinent to the Cube One Framework. Practices prior to the onset of COVID (before March 2020) were obtained retrospectively in addition to practices in the Fall 2022. Because data were obtained at one point in time, the present undertaking is characterized as employing a quasi-longitudinal design. Although three static hypotheses were supported, the cross-lagged panel analysis was not because (only) the relatively new 5-item behavior-based measure, indicated that there was a significant decline in Organizational Performance (t = -3.59; p < .001).
Keywords: management